60 years of absolute standardization of radionuclides by coincidence counting methods in the Romanian metrology laboratory. (August 2021) - Sahagia, Maria; Grigorescu, Enric Leon; Luca, Aurelian; Wätjen, Anamaria Cristina; Ivan, Constantin; Antohe, Andrei; Ioan, Mihail Răzvan
Abstract: This review paper presents the contribution of the Radionuclide Metrology Laboratory (RML) to the development and practical application of the coincidence counting methods. It is also intended to pay tribute to Dr. Enric Leon Grigorescu, the founder of our school of radionuclide metrology. A synthetic treatment of the method, applied to some classes of radionuclides with their common and particular aspects in standardization, is presented: pioneering calculation of instrumental corrections, specific method corrections applied for various types of decay schemes in the variant of efficiency extrapolation, results obtained in international comparisons. Highlights: Development of the coincidence method, efficiency extrapolation. Pioneering original formulae for calculation of instrumental correction. Adequate application of the method to various types of radionuclides. Participation in international comparisons.